DETERMINANTS OF FEMINIZATION OF MIGRATION IN TSHOLOTSHO DISTRICT OF ZIMBABWE - Thebe, Phillip (Advances in Social Sciences Research Journal, 2019)
Tsholotsho District is one of the most significant contributors of migrants in Zimbabwe. Until recently, many of these migrants have been males, with females remaining behind assuming both feminine and masculine roles. Of late, however, females are increasingly venturing in migration expeditions. Why is this the case? Are women taking up economic roles in a society that has largely relegated them to familial responsibilities? What determines their increasing participation in a male dominated practice? These questions are answered in this paper based on a research conducted in Ward 5 of Tsholotsho District in 2016 as well as continued interaction with interlocutors till present day. The results indicated that reasons for feminized migration cut across different realms such as fleeing unfavourable economic conditions, to unite with their migrant spouses, to contribute towards diversifying household income sources, and fleeing unhappy marriages and burdensome familial controls among others. This led the researcher to firmly conclude that feminization of migration is a new reality and future of Tsholotsho’s migration trajectory, one that will be accompanied by resultant problems and opportunities. It will require therefore, careful migration management systems in the country to harness the benefits of this migration typology while offsetting the possible problems.